'The Slate Landscape of Northwest Wales' — A New Industrial World Heritage Site. (2nd January 2023) - Gwyn, David
ABSTRACT: UNESCO's inscription of 'The Slate Landscape of Northwest Wales' as a World Heritage Site in 2021 added for the first time a cultural landscape of quarrying to the World Heritage list, the culmination of a 12-year bid process for Gwynedd Council as the promoting local authority. Its six Component Parts exhibit clear visual and functional relationships with the wider landscape of Snowdonia and the sea, but also significant differences in terms of extraction, processing, workers' settlements and transport. These were described and analysed in a well-produced dossier informed by a comprehensive comparative study, which set out how Wales' robust systems of landscape protection ensured their effective management, and made clear the strong political, business and community support which the bid enjoyed, based on clear goals and ambitions. Inscription makes clear that there is a strong case for other globally significant quarrying landscapes to become World Heritage Sites.